AMNESTY AND FORGIVENESS AS CRIME-LEGAL CATEGORIES (Conferencea, 2022)
Amnesty is a freedom of expression enshrined in a normative legal act adopted by the Senate of the Oliy Majlis of the Republic of Uzbekistan. is a document supported by and is used in court